GroupICA dual regression analysis of resting state networks in a behavioral variant of frontotemporal dementia - Rytty, Riikka; Nikkinen, Juha; Paavola, Liisa; Abou Elseoud, Ahmed; Moilanen, Virpi; Visuri, Annina; Tervonen, Osmo; Renton, Alan; Traynor, Bryan; Kiviniemi, Vesa J.; Remes, Anne M. (Frontiers in Human Neuroscience, 2013)
Functional MRI studies have revealed changes in default-mode and salience networks in neurodegenerative dementias, especially in Alzheimer’s disease. The purpose of this study was to analyze the whole brain cortex resting state networks in patients with behavioral variant frontotemporal dementia by using resting state functional MRI. The group specific resting state networks were identified by high model order independent component analysis and a dual regression technique was used to detect between-group differences in the resting state networks with p<0.05 threshold corrected for multiple comparisons. A y-concatenation method was used to correct for multiple comparisons for multiple independent components, grey matter differences as well as the voxel level. We found increased connectivity in several networks within patients with bvFTD compared to the control group. The most prominent enhancement was seen in the right frontotemporal area and insula. A significant increase in functional connectivity was also detected in the left dorsal attention network, in anterior paracingulate – a default mode sub-network as well as in the anterior parts of the frontal pole. Notably the increased patterns of connectivity were seen in areas around atrophic regions. The present results demonstrate abnormal increased connectivity in several important brain networks including the dorsal attention network and default-mode network in patients with behavioral variant frontotemporal dementia. These changes may be associated with decline in executive functions and attention as well as apathy, which are the major cognitive and neuropsychiatric defects in patients with frontotemporal dementia.